Effect of Substitution the Imported Concentrate by Plant Concentrate on Performance and Blood Chemistry of Broiler Chicks - Atti, Khadiga A. Abdel; Dousa, B.M.; Elseed, A.M. Fadel (Pakistan Journal of Nutrition, 2011)
The experiment was conducted to assess the nutritive value of faba bean (Vicia faba L.var.minor), cowpea (Vigna unguiculata L. Walp), pigeon pea (Cajanus cajan L. Millsp) and alfalfa meal (Medicage Sativa) as a plant concentrate to replace the imported concentrate for broiler diets. The plant concentrate was formulated from faba bean 42%, cowpea 29.98%, pigeon pea 15% and alfalfa meal 5%, lysine 0.8%, methionine 0.72%, calcium 6% and vitamin premix 0.5%, respectively. Two hundred unsexed broiler chicks (Cobb) were used. Four dietary treatments containing 0%, 5%, 10% and 15% plant concentrate were formulated to meet the nutrients requirements as outlined by NRC (1994). The experiment was in a Completely Randomize Design (CRD), 50 birds per treatment with five replication 10 bird/ replicate. The study lasted for six weeks. Parameters measured was feed intake, body weight gain, Feed Conversion Ratio (FCR), pre-slaughter weight, dressing percentage protein efficiency, some blood parameters (glucose, cholesterol, triglyceride, total lipid, total protein, calcium, inorganic phosphorus) and feed cost. Result indicated that dietary inclusion of plant concentrate had significantly (p<0.05) decreased feed intake, final body weight, serum cholesterol and profitability. Birds fed diet containing 5% plant concentrate show similar response to control group (p>0.05) on weight gain, feed conversion ratio, protein efficiency and dressing percentage. However, the dietary treatments had no significant effect (p>0.05) on blood serum glucose, triglyceride, total protein, total lipids, calcium and phosphorus respectively.